Cumulative ecological risk and cyberbullying among college students: a chain mediation model - Miao, Ruikai; Li, Zhuoyang (Frontiers in Psychology, 2024)
Introduction Cyberbullying among college students has been receiving increased research attention. Previous studies have focused primarily on the impact of a single risk factor on cyberbullying among college students. However, individual behavior is influenced by multiple ecosystems simultaneously, including family, school, and peers. To explore the effects of a single risk factor alone is not in line with the reality of everyday life, and the effect of the single risk factor can often be overestimated. Therefore, this study aimed to explore the impact of multiple risk factors, namely cumulative ecological risk, on cyberbullying, while analyzing the mediating roles of belief in a just world and moral disengagement. Methods A survey was conducted among 805 college students from two universities in Hebei Province, China, using the cumulative ecological risk questionnaire, the cyberbullying scale, the belief in a just world scale, and the moral disengagement scale. Results The results showed that: (a) Cumulative ecological risk was positively correlated with moral disengagement and cyberbullying, and negatively correlated with belief in a just world. Belief in a just world was negatively correlated with moral disengagement and cyberbullying. Moral disengagement was positively correlated with cyberbullying; (b) Belief in a just world partially mediated the relationship between cumulative ecological risk and cyberbullying; (c) Moral disengagement partially mediated the relationship between cumulative ecological risk and cyberbullying; (d) Belief in a just world and moral disengagement played a chain mediating role between cumulative ecological risk and college students’ cyberbullying. Discussion This study provides valuable insight for the reduction of cyberbullying behavior among college students, and offers suggestions on how to create a more favorable online environment.